Ghifari alternatif pengentasan anak jalanan: Suatu pendekatan kualitatif - Eko Setyo Pratomo (Universitas Ahmad Dahlan, 2004)
In real life, sleepers social life is most of the time is neglected sleepers, indeed, is youth of the nation who needs lead. This problem become a basic reason for the research so that the researcher can find a formulation to handle sleepers problems. The subject of this research is sleepers under Ghifari treatment. This research based on qualitative research, and examine the way sleeper of life and the treatment alternatives for them. After he research is done, the researcher found out that sleepers have a very unique way of life. Ghifaris's alternative treatment, over the mosque program and the stimulation such capitalization and school fee